Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Era Generasi Milenial: Studi pada Karyawan Kantor PT. Floresindo Ende - Paulino Lucky Puty; Hyronimus Se (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explain: the effect of work motivation partially on employee performance, to explain the effect of the work environment partially on employee performance and to explain work motivation and work environment simultaneously on employee performance. The research method used in this study is to use descriptve analysis with a quantitative approach. The population in this study were millennial employees who work at the PT. Floresindo Ende Office with a sample size of 40 respondents. The data analysis technique used multiple linear regression. Based on the results of the analysis, it can be seen that there is a significant influence between work motivation and employee performance, meaning that with increasing employee work motivation, employee performance will increase. The results of the analysis show that there is a significant influence between the work environment and employee performance, meaning that with better work environment conditions, employee performance will increase. Work motivation and work environment have been shown to have a significant influence on employee performance. This means that with changes in work motivation and work environment, employee performance will change.